Female reproductive tract anatomy of the endangered Arabian oryx (Oryx leucoryx) in Jordan - Eljarah, Abdulhakeem H.; Al-zghoul, Mohd B.; Jawasreh, Khaleel; Bani Ismail, Zuhair A.; Ababneh, Mustafa M.; Elhalah, Ashraf N.; Alsumadi, Maen M. (Italian Journal of Anatomy and Embryology, 2012)
Female reproductive anatomy of the Arabian oryx is unknown. In this study, reproductive tracts of seven female Arabian oryx (aged 2 to 7 years) were examined to characterize their reproductive anatomy. Observations and measurements were obtained in situ from dead animals during necropsy. Animals were allocated into two groups: cycling (n=3; follicles or corpora lutea present) and not-cycling (n=4; follicles or corpora lutea absent). Different reproductive tract segments for each animal in both groups were measured using a digital caliper. The mean, SD and range for each reproductive tract segment were generated and compared between groups. Female oryx reproductive anatomy share some anatomical characteristics with that of domestic ruminants except that the oryx uterus has no distinct uterine body and the cervix has two internal openings for each respective uterine horn. In addition, there were more than 8 rows of caruncles within each uterine horn. There were significant differences in the length and width (P<0.05), but not in height, of both the right and left ovaries between cycling and not-cycling animals (P>0.05). Posterior and anterior vaginal lengths varied between cycling and not-cycling groups (P<0.05). Length of right and left oviducts, left and right uterine horns, cervix and vulva did not vary between cycling and not-cycling groups (P>0.05). Defining this unique morphology of female Arabian oryx reproductive anatomy will help in the development of appropriate reproductive techniques in order to propagate this endangered species and control its reproduction.